Journalistiek in chique verpakking: Over Nederlandse literaire non-fictie - Mourits, Bertram (Department of Dutch and South African Studies, Faculty of English, 2012)
In the 1980s, there was a remarkable rise in what has come to be known as ‘literary non-fiction,’ a genre in which authors (sometimes literary authors, often journalists) told their stories with the use of literary stylistic devices. It was presented as something new by publishers and received as such by the press. Instead of seeing literary non-fiction as a new genre, it makes more sense to trace its history in journalism, especially the New Journalism of the 1950s and 1960s. However, this tradition goes back even further. In the meantime, the popularity of the genre is indicative of a changing attitude towards the relationship between literature and reality.
Keywords: Mak; Westerman; Reve; Hermans; New Journalism; literary history; Dutch